2020
DOI: 10.1080/14680777.2020.1749693
|View full text |Cite
|
Sign up to set email alerts
|

Coloring your prejudices: nail-polish marketing, “slut-shaming,” and feminist activism

Abstract: The Colombian firm Masglo sells nail polish across much of Latin America. Some of its colors have been marketed through words associated with "slut-shaming" and other misogynistic concepts, which stimulated a 2015 consumer debate on Twitter. We analyze the tweets from those exchanges and relate them to feminism, antifeminism, and the status of women in Colombian society. Our results show that female clients, who were the main participants in the debate, mostly favored the company's strategy. Some nodes highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Through a creative use of language that constructs irony, cynicism, and parody, the branding of nail polish and make-up estheticized under the "offline" imaginary attempts to position the brands as modern and attuned with the cosmopolitan, hyperconnected consumer, as well as to create a sense of sophistication in the user. These strategies may not only result in a fleeting smile from the reader but also invite virality, as Barrios et al (2020) found-which in the theme of disconnection accentuates the irony and cynicism.…”
Section: Cosmeticsmentioning
confidence: 88%
“…Through a creative use of language that constructs irony, cynicism, and parody, the branding of nail polish and make-up estheticized under the "offline" imaginary attempts to position the brands as modern and attuned with the cosmopolitan, hyperconnected consumer, as well as to create a sense of sophistication in the user. These strategies may not only result in a fleeting smile from the reader but also invite virality, as Barrios et al (2020) found-which in the theme of disconnection accentuates the irony and cynicism.…”
Section: Cosmeticsmentioning
confidence: 88%
“…These operate alongside sexist, racist and patriarchal artificial intelligence 'experiences' (e.g., Puntoni et al, 2020) underwritten by algorithmic bias (Schroeder, 2020). Alarmingly, some companies promote their products with extremely problematic labels -the Columbian makeup manufacturer, Masglo, being the most obvious example -and this means we are now once again witnessing the use of demeaning tropes and 'abuse' as central to 'marketing strategy' (Barrios et al, 2020). In equal measure, Wei and Bunjun (2020) ask us to remember that marketing, advertising and all the communications vehicles that are available for application can potentially be a force for good.…”
Section: #Metoo and #Timesup In Marketing Academia And Practicementioning
confidence: 99%
“…These operate alongside sexist, racist and patriarchal artificial intelligence 'experiences' (e.g., Puntoni et al, 2020) underwritten by algorithmic bias (Schroeder, 2020). Alarmingly, some companies promote their products with extremely problematic labels -the Columbian makeup manufacturer, Masglo, being the most obvious example -and this means we are now once again witnessing the use of demeaning tropes and 'abuse' as central to 'marketing strategy' (Barrios et al, 2020). In equal measure, Wei and Bunjun (2020) ask us to remember that marketing, advertising and all the communications vehicles that are available for application can potentially be a force for good.…”
Section: #Metoo and #Timesup In Marketing Academia And Practicementioning
confidence: 99%
“…Allies can help create supportive, nurturing and safe environments in universities and industry alike (Thompson-Whiteside et al, 2020). In their paper, Ekant Veer, Kseniia Zahrai and Susannah Stevens along with a host of academic and administratively oriented respondents carefully explain the logic behind our need for allies, where they can help, what we can all do, and the systems that can help us manage the types of discrimination and micro aggressions that many of us will unfortunately face over our careers (see also Barrios et al, 2020). Veer, Zahrai and Stevens register that academia can reflect the best human traits, and some of the worst.…”
Section: The Contents Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation